2018
DOI: 10.15809/irriga.2016v1n01p205-217
|View full text |Cite
|
Sign up to set email alerts
|

Trocas Gasosas E Composição Físico-Química De Vinhos Em Função De Estratégias De Irrigação

Abstract: RESUMOO objetivo deste trabalho foi avaliar as alterações nas variáveis fisiológicas e composição físico-química de vinhos elaborados a partir de videiras submetidas a diferentes estratégias de irrigação. Os tratamentos aplicados foram: irrigação plena -irrigação realizada durante todo o ciclo de produção; irrigação com déficit controlado -onde a irrigação foi interrompida aos 49 dias após a poda, sendo realizadas eventuais irrigações após a interrupção, de acordo com o monitoramento da água no solo; e a irrig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Still in relation to that region, wines originated from grapes from RDI and DI vines showed higher values of alcohol content, malic and lactic acids, flavonols, stilbenes, anthocyanins, epicatechin, epicatechin gallate and procyanidin A2, TPI, and color intensity, and can be classified as aged wine, while wine originated from full irrigation vines showed the highest values of ascorbic and tartaric acids, lowest alcohol content and phenolic compounds in general, and can be classified as young wines. This enabled the production of wines with specific characteristics that should please many consumers with different tastes (Nascimento et al, 2016;Oliveira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Still in relation to that region, wines originated from grapes from RDI and DI vines showed higher values of alcohol content, malic and lactic acids, flavonols, stilbenes, anthocyanins, epicatechin, epicatechin gallate and procyanidin A2, TPI, and color intensity, and can be classified as aged wine, while wine originated from full irrigation vines showed the highest values of ascorbic and tartaric acids, lowest alcohol content and phenolic compounds in general, and can be classified as young wines. This enabled the production of wines with specific characteristics that should please many consumers with different tastes (Nascimento et al, 2016;Oliveira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Nascimento et al (2016) observed in vines under water deficit, reduction in photosynthesis, stomatal conductance and transpiration, while Suassuna et al (2014) verified reductions in gs and E in citrus rootstocks with water restriction. One of the effects of salt stress is the reduction in the availability of water to plants, which causes significant decreases in photosynthetic activity, transpiration and stomatal conductance, and this condition is mainly related to stomatal closure.…”
Section: Resultsmentioning
confidence: 92%